Penerapan model CTL berbantuan media audiovisual untuk meningkatkan hasil belajar tematik terpadu di SD - Agus Irwandy; Yari Dwikurnaningsih; Nur Hidayati (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This research is motivated by the lack of meaningful learning and lack of enthusiasm of students in participating in learning, this has an impact on low student learning outcomes. The purpose of this study is to describe the improvement of learning outcomes of students in learning using Contextual Teaching and Learning (CTL) assisted by audiovisual. The method used in this study is classroom action research, which consists of two cycles. The results of the study show that the classical completeness criterion is ≥85% in cycle two. Classical completeness of social studies content in pre cycle 60%, cycle one 83%, and cycle two 97%, Indonesian language content in pre cycle 69%, cycle one 80%, and cycle two 97%, PPKn lesson content in pre cycle 97% cycle one 97%, and cycle two 100%. Based on the results of these research, the researsh is succesfull.